2021
DOI: 10.1080/21679169.2020.1865451
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of musculoskeletal dysfunction in targets of workplace bullying

Abstract: Background: Workers exposed to bullying often report musculoskeletal symptoms. In this study we have clinically evaluated the prevalence and nature of musculoskeletal dysfunction among a group of workers exposed to bullying and studied the relationship between clinical findings and self-reported musculoskeletal and mental symptoms. Materials and methods: In a cross-sectional study, 144 patients admitted to an outpatient clinic for victims of workplace bullying were assessed with the Global Physiotherapy Examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Hence, victims of ongoing and long-term workplace bullying represent a group characterised with severe negative health complaints, such as musculoskeletal complaints [ 6 ], common mental disorders (CMD) in the form of anxiety and depression [ 2, 7 ], and even symptoms of post-traumatic stress [ 8, 9 ]. The negative health effects may become long-lasting, and some longitudinal studies have confirmed that these negative outcomes may persist over several years [ 10, 11 ], and long after the bullying may have ceased [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, victims of ongoing and long-term workplace bullying represent a group characterised with severe negative health complaints, such as musculoskeletal complaints [ 6 ], common mental disorders (CMD) in the form of anxiety and depression [ 2, 7 ], and even symptoms of post-traumatic stress [ 8, 9 ]. The negative health effects may become long-lasting, and some longitudinal studies have confirmed that these negative outcomes may persist over several years [ 10, 11 ], and long after the bullying may have ceased [ 12 ].…”
Section: Introductionmentioning
confidence: 99%